The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1362168818787546
|View full text |Cite
|
Sign up to set email alerts
|

Oral corrective feedback: Pre-service English as a second language teachers’ beliefs and practices

Abstract: This study investigated the relationship between pre-service English-as-a-second-language (ESL) teachers’ pedagogical beliefs and their actual teaching practices. To determine the nature of this relationship, 99 teachers-in-training with little or no teaching experience were asked to complete a questionnaire seeking information about their teaching beliefs, particularly about oral corrective feedback (i.e. teachers’ responses to students’ language errors). The teachers’ responses were subjected to an explorato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 56 publications
5
37
2
6
Order By: Relevance
“…The observed teachers' individual performance (see Table 3) showed that a majority of them, as in the previous studies (e.g., Jean & Simard, 2011;Kartchava et al, 2018;Lee, 2013), left more than half of the errors untreated. This was particularly so in the case of advanced learners; the teachers, except for Teacher 5, provided fewer corrections for the advanced learners in practice.…”
Section: Amount Of Correctionsupporting
confidence: 69%
See 3 more Smart Citations
“…The observed teachers' individual performance (see Table 3) showed that a majority of them, as in the previous studies (e.g., Jean & Simard, 2011;Kartchava et al, 2018;Lee, 2013), left more than half of the errors untreated. This was particularly so in the case of advanced learners; the teachers, except for Teacher 5, provided fewer corrections for the advanced learners in practice.…”
Section: Amount Of Correctionsupporting
confidence: 69%
“…This finding points to the need for dispelling teachers' misconceptions about how learners may react to correction and informing them about the results of studies and the benefits of other types of feedback for different proficiency groups in the framework of professional development programs, which, as pointed out by Borg (2003), play a determining role in forming teachers' cognitive processes. As Kartchava et al (2018) noted, teachers' limited knowledge "about how, when, and in what amounts to provide feedback prevents them from reconciling their beliefs with classroom practices" (p. 238).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Long (1983) found that the most common method teachers utilize to correct students is restatement. Error correction has been a controversial type of feedback in SLA studies (Azad 2016;Kartchava & Gatbonton, 2020;McDonough & Sato, 2019). One group declares that too often correcting the errors made by students may break down their talk to pieces without favoring complete and coherent production, but another group testified that error correction can help English learning.…”
Section: Literature Reviewmentioning
confidence: 99%